Penerapan Model Pembelajaran Kooperatif Tipe (TGT) untuk Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Matematika - Santika, Rani; Noperman, Feri (Universitas Bengkulu, 2024)
This study aims to describe the implementation of the Teams Games Tournament (TGT) cooperative model assisted by visual aids and to analyze the increase in student learning outcomes. This type of Classroom Action Research (PTK) with the research subject was the teacher and fifth-grade students at SDN 44 Bengkulu Selatan, totaling 12 students. The research instrument is the observation sheet and test sheet. The data were analyzed using the formula for the average score, and the formula for the average value and percentage of classical learning completeness. The results showed that the implementation of the model in the first cycle was 62.5 with category B (good), and experienced an increase in cycle II 77 with very good category (SB). Student learning outcomes in the first cycle of classical learning mastery were 75% with sufficient criteria (C), an increase in the second cycle of 92% with good criteria (B). In conclusion, the application of the Teams Games Tournament (TGT) cooperative learning model assisted by visual aids can improve student learning outcomes in learning mathematics.